Design and Experiment of a Prototype Electronic Control Unit Direct Injection Fuel System Arduino-Based for 2-stroke Spark Ignition Engine - Darwin Rio Budi Syaka; Ade Tiya Purwoko; Sopiyan Sopiyan (Automotive Experiences, 2022)
The development of technology on the 2-stroke direct-injection spark-ignition engine is expected to be a solution to optimize engine performance and reduce exhaust pollution. The fuel injection system in the operation of the spark-ignition engine is controlled by the Electronic Control Unit (ECU), so this study aims to design and experiment with a prototype of an Arduino-based direct injection fuel injection electronic control unit for 2-stroke spark-ignition engines. This research method begins with the design of an electronic control unit prototype that is selected for easy setup and low cost. Then, experiments were conducted on variations in injection timing and injection duration, which are the two main parameters of the fuel system to determine their effect on engine performance. This data is then used as a basis for setting the amount of fuel injected. The results show that there is an optimal performance under certain conditions from setting the injection timing and injection duration which is easily applied to the open-source code setting of this electronic control unit.